Assessment of cognitive skills in dermatology during internship - Prasad, Arakali Lakshminarayana Shyam; Shanmugam Reddy, Praveen Kumar (International Journal of Research in Dermatology, 2017)
Background: Skin problems constitute a significant percentage of all medical problems, despite which training in recognition and treatment of dermatological disorders during the MBBS course remains abysmal. The situation is compounded due to non-inclusion of dermatology in the final examinations, which results in students having little motivation to learn about this important subject. This study was designed to test whether the present internship training offered in dermatology succeeds in imparting cognitive skills related to common skin problems. Methods: This was done by means of a pre- and post-test administered before and after their posting. A set of 20 questions were administered to all interns on the first day of their postings as a pre-test and the post-test was given on the last day, after completion of their two week posting. Results: The results of this preliminary study suggest that there is considerable improvement after their training. The paired t test, the t value was found to be -16.13 with a p value of <0.001, which was statistically significant. Conclusions: It is possible that use of a pre- and post-test focuses their attention on common entities and thus could be used to improve cognitive skills. To the best of our knowledge a similar study has not been reported from the Indian subcontinent.